4. Tureckie soft power w Kirgistanie .......... 343 - Osierda, Kinga (Kirgistan – oblicza transformacji, 2020)
TURKISH SOFT POWER IN KYRGYZSTANAfter the collapse of the Union of Soviet Socialist Republics (USSR) in some of former republics, religion and culture became two indicators of social identification as elements of nationality and national identity linked together. In the context of the countries mentioned in the title, Turkey and Kyrgyzstan, religious cooperation has taken on an important dimension, which is visible now on several levels of social life. Turkey, taking advantage of its position in relation to the countries of Central Asia, soon after the collapse of the Soviet Union began to actively operate in this region. Using education and religion as a soft power tool, it currently plays an important role especially in these two spheres.The purpose of this work is, among others, showing the sources of Turkish-Kyrgyz relations in the 21st century and presenting some examples of Turkey’s soft power in Kyrgyzstan.